Breaking the barriers: addressing dental students bullying by medical counterparts and promoting a collaborative learning environment - Qamar, Wajiha; Qayum, Mehran; Nisar, Anita (Frontiers in Education, 2023)
The study question on the bullying of dental students by their medical counterparts is of the utmost significance due to the policy implications and the necessity for additional research. Despite anecdotal evidence showing instances of competitiveness and exploitation between dental and medical students, there is an absence of comprehensive studies on the incidence and impact of bullying specifically targeted against dental students. This research gap is concerning since bullying has a negative impact on people’s mental health, academic success, and professional development. This review provides an in-depth study of the matter, allowing the policymakers better understand the scope and dynamics of bullying among medical and dental students, to enable them develop specialized policies and programs to address the problem.